Arachidonic acid as a potentially critical nutrient for vegetarians and vegans – position paper of the Research Institute for Plant-based Nutrition (IFPE) - Stine Weder; Sandra Müller; Christine Dawczynski; Markus Keller (Lipids in Health and Disease)
Abstract The long-chain polyunsaturated fatty acid arachidonic acid (ARA, 20:4n-6) is virtually non-existent in plant foods. Concerns have therefore been raised that a predominantly plant-based diet, i.e., a vegetarian or vegan diet, could lead to ARA deficiency. ARA is discussed as conditionally essential, particularly in early infancy and childhood. Therefore, the authors of this position paper provide an overview of the state of scientific research on ARA for Western countries, with a special focus on risk groups, e.g., pregnant and breastfeeding women, infants, and children. We discuss whether ARA is potentially essential in critical life stages and whether a plant-based diet is appropriate in relation to ARA. Preliminary recommendations are derived on the basis of the available literature: healthy adults and pregnant and lactating women are able to synthetize ARA from linoleic acid (LA, 18:2n-6) and, therefore, do not require ARA supplementation, even with plant-based diets. Owing to the importance of ARA in early childhood, infants should be breastfed or given ARA-containing formula. According to current data, it can be assumed that infants, children, and adolescents are also capable of producing sufficient amounts of ARA regardless of their diet. However, these data are sparse. Furthermore, owing to the lack of reference ranges, there are no suitable test methods for diagnosing deficiency. All in all, owing to insufficient data, these recommendations are preliminary, and further studies with risk groups are urgently needed.